2010
DOI: 10.1007/s10695-009-9351-5
|View full text |Cite
|
Sign up to set email alerts
|

Roach (Rutilus rutilus) reproductive cycle: a study of biochemical and histological parameters in a low contaminated site

Abstract: Fish reproduction is subjected to worrying trends in many aquatic environments. In this study, we report the absence of histological and biochemical alterations in fish sampled in a low contaminated site (characterised by the absence of detectable oestrogenic activity and mutagenicity in sediment extracts). A total of 474 roach (Rutilus rutilus) were monthly sampled during 18 months, and no intersex fish were recorded after careful histological examination, thus indicating that the incidence of this phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…In the same species, Gillet and Quetin (2006) also showed that an increase in water temperature of 1°C modified the life-history strategy of roach in Lake Geneva, by accelerating the development of gonads and affecting spawning date. Geraudie et al (2010) also reported earlier gonad maturation in female and male roach due to elevated temperature recorded during winter time.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the same species, Gillet and Quetin (2006) also showed that an increase in water temperature of 1°C modified the life-history strategy of roach in Lake Geneva, by accelerating the development of gonads and affecting spawning date. Geraudie et al (2010) also reported earlier gonad maturation in female and male roach due to elevated temperature recorded during winter time.…”
Section: Discussionmentioning
confidence: 72%
“…The results of the present study, combined with previous data on reproductive and demographic traits of bullhead (Abdoli et al 2005(Abdoli et al , 2007Reyjol et al 2009), suggest possible deleterious effects of warming on its population dynamics. According to Geraudie et al (2010), reproduction is a key mechanism for the survival of a given species. The consequences on population and species survival could be severe unless development of phenotypic plasticity within a generation over multiple years or genetic adaptation over generations might produce individuals more tolerant to a warmer future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, comparative studies on sex determination in distinct fish groups, revealed that the molecular mechanisms for sex determination can be temperaturedependent, even in species with a firm genotypic sex determination [reviewed in Ospina-Alvarez and Piferrer, 2008]. Another environmental factor associated with intersexuality in wild fish is the presence of endocrine-disrupting chemicals (EDCs) [Geraudie et al, 2009]. The relation between hermaphroditism and the anthropogenic impact on the rivers is now well established and was reported for several species of freshwater fish [Jobling and Tyler, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…The fish were then classified as male, female or hermaphrodite. The maturation status was assessed by the presence of characteristic gametogenic stages categorized according to Paull et al [2008] and Geraudie et al [2009].…”
Section: Gonad Preparation and Analysismentioning
confidence: 99%